Radical Voronoï tessellation from random pack of polydisperse spheres: Prediction of the cells' size distribution. (February 2019) - Depriester, Dorian; Kubler, Régis
Abstract: This paper investigates the relevance of the representation of polycrystalline aggregates using Radical Voronoï (RV) tessellation, computed from Random Close Packs (RCP) of spheres with radius distribution following a lognormal distribution. A continuous relationship between the distribution of sphere radii with that of RV cell volumes is proposed. The stereology problem (deriving the 3D grain size distributions from 2D sections) is also investigated: two statistical methods are proposed, giving analytical continuous relationships between the apparent grain size distribution and the sphere radius distribution. In order to assess the proposed methods, a 3D aggregate has been generated based on a EBSD map of a real polycrystalline microstructure. Highlights: Random packs of polydisperse spheres have been computed with LAMMPS. Radical Vorono tessellation have been performed on each pack. Cell sizes have been statistically characterized in each case. Relationships between spheres' population and cell sizes are derived. The bias introduced by cross sectioning (2D apparent sizes) is investigated.